PENGARUH SKEPTISME PROFESIONAL TERHADAP PERILAKU DISFUNGSIONAL AUDITOR (STUDI EMPIRIS PADA KAP SE KOTA DENPASAR) - I.A Rayhita Santhi (Jurnal Widya Akuntansi dan Keuangan, 2021)
This study aims to analyze the effect of professional skepticism on auditor dysfunctional behavior. The population in this study were 91 auditors registered with KAP in Denpasar City, from 91 questionnaires distributed, 80 questionnaires were returned and could be processed further. The result of this study is that professional skepticism has a negative and significant effect on auditor dysfunctional behavior.